University Calculus: Early Transcendentals (3rd Edition)

Published by Pearson
ISBN 10: 0321999584
ISBN 13: 978-0-32199-958-0

Chapter 2 - Section 2.2 - Limit of a Function and Limit Laws - Exercises - Page 66: 28


$\lim\limits_{t \to -1}\frac{(t^{2}+3t+2)}{(t^{2}-t-2)} = -\frac{1}{3}= 0.33$

Work Step by Step

Simplify: $\frac{(t^{2}+3t+2)}{(t^{2}-t-2)} =\frac{(t+1)(t+2)}{(t-2)(t+1)} = \frac{(t+2)}{(t-2)}$ Now, $\lim\limits_{t \to -1}\frac{(t^{2}+3t+2)}{(t^{2}-t-2)} = \lim\limits_{t \to -1}\frac{(t+2)}{(t-2)} = -\frac{1}{3}= 0.33$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.